Natural History of Reproductive Complications (Menstruation, Including Cancer, and Menopause) - Roger Hart (Fertility & Reproduction, 2023)
A lifelong reproductive health plan is recommended for women with PCOS, with a focus on preconception risk factors including prevention of weight gain and optimisation of fertility. Metabolic risk factors, diabetes, cardiovascular disease, and sleep disorders are all increased in PCOS and screening and management is recommended. PCOS should be considered a high-risk condition in pregnancy with women identified and monitored. An increased premenopausal risk of endometrial cancer should be recognised. Depressive and anxiety symptoms are significantly increased and should be screened for in all women with PCOS, with psychological assessment and therapy as indicated. Shared decision making, self-empowerment and integrated models of care should be developed, funded, and evaluated. Supported healthy lifestyle remains vital throughout the lifespan in PCOS, with a strong focus on overall health, prevention of weight gain and if required on weight management. Combined oral contraceptive pills are first line pharmacological treatment for menstrual irregularity and hyperandrogenism, with no specific recommended preparation, and a preference for lower dose preparations and those with less side-effects. Metformin is recommended primarily for metabolic, although it is not routinely recommended for use in pregnant women with PCOS.